State-Centric versus Human Resource–Centric Khilafah: A Comparative Analysis - Tobroni, Faiq (LP2M UIN Sayyid Ali Rahmatullah Tulungagung, 2025)
The concept of the khilafah has been reduced to a form of governance intended to replace Pancasila. As part of Islamic history, however, the khilafah carries significant strategic implications for the development of the Muslim community. This article examines the contestation of the khilafah concept between state-centric and human resource–oriented, contextual perspectives, and the extent to which a human resource–oriented reinterpretation of the khilafah can be offered as an alternative beyond the nation-state framework. Methodologically, the study employs a critical–interpretive discourse analysis based on a systematic review of academic literature and primary discursive data. The literature is classified into three groups: works that support the khilafah as a political system, works that reject it through the lens of modern state theory, and works that offer contextual reinterpretations of the concept. The primary data consist of public interviews and statements by Yudian Wahyudi, which are analyzed through thematic categorization, comparative interpretation, and contextual analysis. The findings demonstrate that while HTI's discourse remains confined to a rigid state-centric paradigm, Yudian's framework reconceptualizes the khilafah not as a system of state power but as an ethical and managerial responsibility oriented toward the development of qualified, competent, and morally accountable human resources capable of managing diversity (ikhtilāf) and responsibility (amanah). Theoretically, this reinterpretation advances a post-nation-state model of Islamic political ethics by positioning the khilafah as a portable moral vocabulary applicable across diverse political and cultural contexts for human development.